ANALISIS YURIDIS NORMATIF TERHADAP PERATURAN BERSAMA MENTERI AGAMA DAN MENTERI DALAM NEGERI NOMOR 9 TAHUN 2006 DAN NOMOR 8 TAHUN 2006 - Bambang Hermanto (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Currently on the one side of the issue of religious differences often cause of conflict in society. To realize the pattern of a positive relationship is basically a shared of responsibility religious communities, local governments and government. With the enactment of Joint secretary of Religious Affairs the Ministry of home affairs on Guidelines for Task Regional Head / Deputy Head of the Maintenance of Religious Harmony, and the constuctions of Houses of Worship in the emporverment forum on religious harmony and the constructions of houses of Worship is in the public and the government has new rules in an effort embodiment religious harmony , In terms of the hierarchy of laws, regulation and Minister for home Affairs joinr MORA about guidelines Regional Head of religious harmony, FKUB role and establishment of houses of worship, if it is related to the type and hierarchy of legislation decree or regulation of the minister usually not binding outside the existing institutions in Under the authority of the ministry. In addition, based on the type and hierarchy of applicable legislation or regulation can not find the decree of the ministter in the herarchy of exiting legisltaion. Based on the various articles in the joint rules be be understood that the issue of the establishing a houses of worship was the basis of teh legal arrangments attempt to achieve religious harmony. However, this should not binder or distort the purpose of the enactment of licensing policy the establishment of houses of the synagogue , however, principally because it is done it primarily for protect the human rights, particularly freedom of religion